2014
DOI: 10.1038/srep05426
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure, strain and physical properties in oxide nanocomposite films

Abstract: We, using LSMO:ZnO nanocomposite films as a model system, have studied the effect of film thickness on the physical properties of nanocomposites. It shows that strain, microstructure, as well as magnetoresistance strongly rely on film thickness. The magnetotransport properties have been fitted by a modified parallel connection channel model, which is in agreement with the microstructure evolution as a function of film thickness in nanocomposite films on sapphire substrates. The strain analysis indicates that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 52 publications
3
37
1
Order By: Relevance
“…Combined with the corresponding Fast Fourier Transaction (FFT) patterns (Figs. 2(c) and 2(d)), a good epitaxial relationship between the SRO nanopillar and the ZnO matrix can be identified: ZnO(0002) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) H jj SRO(011)(100) pc , which is consistent with the EDP analysis. A well-defined two-phase heterointerface was observed, and no secondary phase was found at the boundaries.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Combined with the corresponding Fast Fourier Transaction (FFT) patterns (Figs. 2(c) and 2(d)), a good epitaxial relationship between the SRO nanopillar and the ZnO matrix can be identified: ZnO(0002) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) H jj SRO(011)(100) pc , which is consistent with the EDP analysis. A well-defined two-phase heterointerface was observed, and no secondary phase was found at the boundaries.…”
supporting
confidence: 73%
“…13,14 Meanwhile, the vertical strain originated from the columnar hetero-interfaces begins to control the growth behaviors of the component phases with increasing the film thickness. 15,16 The significant effects on nanostructure growth triggered by the strains from the in-plane and outof-plane directions, respectively, are quite complicated, which depends on the different structural information in the nanocomposite films.…”
mentioning
confidence: 99%
“…In fact, the growth of self-assembled columnar nanostructures embedded into epitaxial thin films, allowing the tuning of the material functionalities, has opened unprecedented prospects for potential applications in ferroelectrics, thermoelectrics, and magnetoelectrics devices and high temperature superconductors. [1][2][3][4][5] In particular, the possibility to strongly improve flux pinning in YBa 2 Cu 3 O 7−x films by introducing nano-scale artificial pinning centres (APCs) has attracted a remarkable interest in recent years. In fact, by enhancing the transport film performances as a function of both the applied magnetic field intensity and the direction, it is possible to reach the current requirements needed in a wide range of present and future applications.…”
mentioning
confidence: 99%
“…18,19 Another way is to form a three-dimensional mesoscale structure, in which one constituent TMO plays the role of a matrix and the other serves as a pillar. 20,21 Toward the understanding of the coupling mechanism in these heterostructure materials, the ordered double perovskite Bi 2 FeMnO 6 (BFMO), which can be regarded as an extreme case of particular-matrix heterostructure, 22 is particularly interesting, with the potential of improved electric and magnetic properties. Experimentally, the BFMO can be synthesized (see experimental method) through the dilution of the Fe-sublattice by Mn in BiFeO 3 while the end member BiMnO 3 , isostructural to BFeO 3 , is ferromagnetic below ∼105 K. 8,23 Earlier studies of BFMO thin films reported a weak enhancement of magnetic moment up to ∼0.18 µ B /f.u.…”
mentioning
confidence: 99%